MENINGKATKAN PEMAHAMAN NILAI KARAKTER DAN PERILAKU POSITIF ANAK MELALUI PSIKOEDUKASI DI KOMUNITAS X - Aditya Aditya; Nurhayati Nurhayati; Valensia Valensia; Agustina Agustina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The Covid-19 pandemic has brought behavioral changes for groups of children. Due to social restrictions, 28% of 371 children found behavioral problems, 54% of low prosocial behavior, and 42% of high emotional symptoms (Nonweiler et al., 2020). In Indonesia, the results of the analysis of Kusuma and Sutapa (2020) in their research found that in general children's social-emotional behavior during online learning was less cooperative because they rarely played together, lacked tolerance, boredom, and sadness. The emergence of behavioral problems that described negative behaviors is a challenge for every family or community or institution engaged in child assistance such as Community X in the city of Bekasi. Volunteers both personally and institutionally reduce visits and interactions with children in Community X as partners and even hold more activities online during the Covid-19 pandemic. Based on the results of observations with several Community X administrators and observations of the humanitarian project team, some children display negative behaviors. The above conditions show the importance of debriefing for children starting from increasing the understanding of positive behaviors and supporting the vision and mission of Community X. This became the basis for the Humanitarian Project with the title “Improving the understanding of character values through psychoeducation in Community X